A framework for reverse logistics: the case of post-consumer carpet in the US. Issue 4 (2nd November 2015) - Cline, Anthony; LeMay, Steve; Helms, Marilyn M
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to apply the goals and processes of reverse logistics related to disposal and renewal to an industry example, in this case, the tufted carpet manufacturing industry. With an industry-wide coalition, the Carpet America Recovery Effort (CARE), the carpet industry offers lessons for other industries on how to create new products from waste, how to develop systems to process this waste, how to encourage the development of infrastructure for reprocessing and how to remove barriers to recovery. A major part of the US floor covering cluster is headquartered around Dalton, Georgia. The industry has formed a coalition to divert manufactured carpet from landfills and find other uses for used carpet. This industry-wide coalition, known as the Carpet America Recovery Effort, offers many lessons for other industries on creating new products from waste, developing systems to process this waste, encouraging the development of infrastructure for reprocessing and removing barriers to recovery. Design/methodology/approach – Academics have proposed several frameworks for examining reverse logistics. In this study, the framework developed by de Brito and Dekker (2004) is utilized because it focuses on essential forces in reverse logistics, asking four simple questions: Why? What? How? and Who? To this list, is added a question: Where? This modified framework is applied to the carpet manufacturing industry, focusing on post-consumer carpet. Findings – The carpet industry is becoming a model for developing renewal supply chains that take waste products and create new ones. Although disposal remains the largest part of the end-of-use supply chain for carpet, this is changing, though not rapidly enough to suit the industry. Originality/value – This case focuses on what the industry is currently doing and on the impediments it has encountered in developing these chains. Renewal chains may well dominate the future of reverse logistics in the industry, but much work remains. The paper concludes with a discussion and areas for future research.